Capability of Tissue Stem Cells to Organize into Salivary Rudiments - Kenji Okumura; Masanori Shinohara; Fumio Endo (Stem Cells International)
Branching morphogenesis (BrM), an essential step for salivary gland development, requires epithelial-mesenchymal interactions. BrM is impaired when the surrounding mesenchyme is detached from the salivary epithelium during the pseudoglandular stage. It is believed that the salivary mesenchyme is indispensable for BrM, however, an extracellular matrix gel with exogenous EGF can be used as a substitute for the mesenchyme during BrM in the developing salivary epithelium. Stem/progenitor cells isolated from salivary glands in humans and rodents can be classified as mesenchymal stem cell-like, bone-marrow-derived, duct cell-like, and embryonic epithelium-like cells. Salivary-gland-derived progenitor (SGP) cells isolated from duct-ligated rats, mice, and swine submandibular glands share similar characteristics, including intracellular laminin and α6β1-integrin expression, similar to the embryonic salivary epithelia during the pseudoglandular stage. Progenitor cells also isolated from human salivary glands (human SGP cells) having the same characteristics differentiate into hepatocyte-like cells when transplanted into the liver. Similar to the dissociated embryonic salivary epithelium, human SGP cells aggregate to self-organize into branching organ-like structures on Matrigel plus exogenous EGF. These results suggest the possibility that tissue stem cells organize rudiment-like structures, and the embryonic cells that organize into whole tissues during development are preserved even in adult tissues.